2011
DOI: 10.1007/s00431-011-1570-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice

Abstract: Cerebral palsy (CP) is the most common physical disability in early childhood. The worldwide prevalence of CP is approximately 2–2.5 per 1,000 live births. It has been clinically defined as a group of motor, cognitive, and perceptive impairments secondary to a non-progressive defect or lesion of the developing brain. Children with CP can have swallowing problems with severe drooling as one of the consequences. Malnutrition and recurrent aspiration pneumonia can increase the risk of morbidity and mortality. Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 52 publications
6
51
0
7
Order By: Relevance
“…Such findings indicate that that the accurate clinical diagnosis of dysphagia may not be sufficient in some cases, i.e., probably swallow dysfunctions are not being timely identified and approached, increasing the risk of complications. Similar findings were observed by other authors ( 11 , 18 ) who have concluded that the clinical diagnostic evaluation may fail to detect some difficulties in the swallow process. However, it is observed that a robust methodology with consistent techniques and appropriate standardization of the food consistencies was not utilized in such studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such findings indicate that that the accurate clinical diagnosis of dysphagia may not be sufficient in some cases, i.e., probably swallow dysfunctions are not being timely identified and approached, increasing the risk of complications. Similar findings were observed by other authors ( 11 , 18 ) who have concluded that the clinical diagnostic evaluation may fail to detect some difficulties in the swallow process. However, it is observed that a robust methodology with consistent techniques and appropriate standardization of the food consistencies was not utilized in such studies.…”
Section: Discussionsupporting
confidence: 91%
“…The videofluoroscopy ( 11 ) was performed according to standardized protocol utilizing a remotely commanded seriograph (VMI; Serimatic Pulsar Plus ® , Lagoa Santa, Brazil), with the table tilted to 90º ( 13 , 14 ) . Lateral radiological view was utilized, as it better shows the airways patency ( 15 ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the evaluation and treatment of drooling in children with cerebral palsy have been extensively studied [93], there is relatively little information about drooling in children with NMDs. Lip strengthening training in children with myotonic dystrophy was found to increase lip force and lip force endurance, but did not influence drooling [94].…”
Section: Recommendationsmentioning
confidence: 99%
“…
Дитячий церебральний параліч (ДЦП) залишається однією з найактуальніших проблем неврології дитячого віку та причин інвалідності дітей [3, 5,13]. Останніми роками частота ДЦП не має тенденції до зниження внаслідок дії таких чинників, як удосконалення методів виходжування й зниження смертності недоношених дітей та новонароджених з екстремально низькою масою тіла [3,11]. Цей термін об'єднує групу синдромів, Îãëÿä ë³òåðàòóðè / Review of Literature ® що виникли внаслідок порушення розвитку або ушкодження центральної нервової системи [13].
…”
unclassified